Regression Analysis to Determine the Reserve Strength Ratio of Fixed Offshore Structures - Iskandar, Nabila Aisyah (Universiti Teknologi PETRONAS, 2013)
This study estimates the Reserve Strength Ratio (RSR) of fixed offshore structures with the utilization of regression analysis, which is capable in replacing the conventional expensive and time consuming methods currently adapted in the oil and gas industry. Offshore structures from the three regions of Malaysian Waters namely Peninsular Malaysia, Sarawak and Sabah were used to perform the analysis of different jacket configurations and sea-states accordingly. The pushover analysis of this study was performed by SACS program version 5.3 and the regression analysis was done using Microsoft Excel. Finding has revealed that regression analysis is able to produce regression coefficients to formulate non-linear regression equations fitting to the set of data to estimate the platform RSR.